2020
DOI: 10.17221/232/2019-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Selected physical parameters and chemical compounds of different types of tomatoes

Abstract: The aim of this experiment was to compare selected types and varieties of tomatoes (‘Beef-red’, ‘Beef-orange’, ‘Olmeca’, ‘Malinowy’, ‘Cherry-red’, ‘Cherry-mini malina’, ‘Cherry-orange’, ‘Papryczkowy’) by examining their chemical composition and identifying the selected physical properties. The research material consisted of tomato fruit purchased on the regional market (Warmia and Mazury voivodeship, Poland) from one producer. An analysis of colour and texture measurement was performed. Moreover, the total dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…In our study, the concentration of lycopene in cherry tomatoes was considerably higher than that detected in big size tomatoes, regardless of tomato colour, but lower concentration was determined for yellow tomatoes. The results reported here are in line with previous studies (Markovic et al, 2006;Bojarska et al, 2020) in which lycopene concentration in fresh tomatoes ranged from 1.82 to 11.19 mg•100 g -1 wet weight; similar also to values reported by Asensio et al (2019) and Coyago-Cruz et al (2019) as well to our previous results (Dûma et al, 2018), but lower than those reported by Marti et al (2016). The lycopene concentration was on average 30% higher in red tomatoes than in brown tomatoes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, the concentration of lycopene in cherry tomatoes was considerably higher than that detected in big size tomatoes, regardless of tomato colour, but lower concentration was determined for yellow tomatoes. The results reported here are in line with previous studies (Markovic et al, 2006;Bojarska et al, 2020) in which lycopene concentration in fresh tomatoes ranged from 1.82 to 11.19 mg•100 g -1 wet weight; similar also to values reported by Asensio et al (2019) and Coyago-Cruz et al (2019) as well to our previous results (Dûma et al, 2018), but lower than those reported by Marti et al (2016). The lycopene concentration was on average 30% higher in red tomatoes than in brown tomatoes.…”
Section: Discussionsupporting
confidence: 93%
“…It was concluded that small-fruited tomatoes have the highest concentration of phenolic compounds, especially in autumn, and the concentration is lower by ~5% in spring. The results reported here are in line with the data presented by Asensio et al (2019) and Alenazi et al (2020), and slightly lower than in other reports (Dûma et al, 2018;Bojarska et al, 2020). However, it should be noted that the comparison is often difficult due to the great influence of agronomic factors such as varieties, growing conditions and harvesting time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It may enhance pink tomato flavor by small increasing the concentrations of fatty acid and carotenoid derivatives without sacrificing yield or fruit size. Luckly, Yang et al was able to generate pink-fruited tomato plants using CRISPR/Cas9-mediated targeted mutagenesis of SlMYB12 [34].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Delgadillo-Díaz et al [ 7 ] investigated the physicochemical characteristics and biological activity of S. lycopersicum L. and S. pimpinellifolium L. in different cropping systems. Similarly, Bojarska et al [ 8 ] investigated the physicochemical properties of different tomato cultivars, including small-sized tomatoes and concluded that the lower hardness and high biological activity of small-fruited tomatoes compared to commercial tomatoes. This indicates that small-sized tomatoes are an attractive source of health-promoting properties.…”
Section: Introductionmentioning
confidence: 99%